The tension between national and international interest in curriculum policymaking: an Indonesian higher education experience - Subkhan, Edi; Budiyono, Budiyono; Johan, Riche Chyntia (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
This article critically examines the Indonesian higher education curriculum policymaking officially issued by the government in 2020. Employing the framework of critical policy analysis, we scrutinize the manual of curriculum policymaking and its associated influential documents that have significantly shaped Indonesian higher education. Our analysis reveals a tension between national and international interests in curriculum policymaking. This tension, and the resulting overlap of these interests, has given rise to several issues, notably the deterioration of the academic and democratic climate on campuses due to academic humiliation and intervention, overload curriculum design, a curriculum that prioritizes skills over knowledge, and strict control over curriculum. Furthermore, the inflexible and overloaded curriculum design has resulted in challenges during implementation. This suggests that the policy exhibits a limited potential to empower graduates to effectively serve both national and international interests. Abstrak Artikel ini mengkritik pembuatan kebijakan pengembangan kurikulum untuk perguruan tinggi di Indonesia yang resmi dikeluarkan oleh pemerintah pada tahun 2020. Dengan menggunakan kerangka analisis kebijakan kritis, peneliti memfokuskan mengkaji buku panduan pengembangan kurikulum untuk Pendidikan tinggi dan dokumen terkait yang secara signifikan memengaruhi arah pendidikan tinggi di Indonesia. Analisis kami mengungkap adanya tegangan antara kepentingan nasional dan internasional dalam pembuatan kebijakan kurikulum. Tegangan ini, dan juga tumpang tindih dari kedua kepentingan tersebut, telah membuahkan beberapa masalah, terutama penurunan iklim akademis dan demokratis di kampus akibat adanya perendahan akademik dan intervensi, kurikulum yang sarat materi, lebih menekankan keterampilan ketimbang pengetahuan, dan kontrol ketat terhadap kurikulum. Selain itu, desain kurikulum yang kaku dan sarat materi juga menimbulkan menyulitkan implementasinya. Dengan demikian dapat disimpulkan bahwa bahwa kebijakan kurikulum untuk perguruan tinggi dari pemerintah ini terbatas potensinya dalam memberdayakan lulusan agar dapat berkontribusi bagi kepentingan nasional dan internasional.